The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/nano10091796
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Heat Transfer and Pressure Drop in Microchannel Heat Sink Using Al2O3 and ZrO2 Nanofluids

Abstract: A new micro heat exchanger was analyzed using numerical formulation of conjugate heat transfer for single-phase fluid flow across copper microchannels. The flow across bent channels harnesses asymmetric laminar flow and dean vortices phenomena for heat transfer enhancement. The single-channel analysis was performed to select the bent channel aspect ratio by varying width and height between 35–300 μm for Reynolds number and base temperature magnitude range of 100–1000 and 320–370 K, respectively. The bent chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Many researchers around the world have focused nanofluids as they provide the possibility of increased heat transfer for various purposes including cooling of thermal power plants, electronics, manufacturing and transportation. Most of the nanofluids’ works as heat transfer fluid (HTF) have concentrated on utilizing typical 2D nanoparticles such as graphene or conventional nanoparticles namely copper, silver, gold, aluminum oxide, copper oxide and silicon carbide [ 1 , 2 , 3 , 4 ]. For example, Wang et al [ 5 ] showed a thermal conductivity enhancement of 14.2% using graphene nanoparticles in ethylene glycol base fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers around the world have focused nanofluids as they provide the possibility of increased heat transfer for various purposes including cooling of thermal power plants, electronics, manufacturing and transportation. Most of the nanofluids’ works as heat transfer fluid (HTF) have concentrated on utilizing typical 2D nanoparticles such as graphene or conventional nanoparticles namely copper, silver, gold, aluminum oxide, copper oxide and silicon carbide [ 1 , 2 , 3 , 4 ]. For example, Wang et al [ 5 ] showed a thermal conductivity enhancement of 14.2% using graphene nanoparticles in ethylene glycol base fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Flow on the micro-scale exhibits dissimilar properties from the flow on the macro scale; albeit, some disagreements amongst researchers exist regarding this. Nevertheless, the governing equations used for modelling the simulation of the novel heat sinks and standard k-epsilon flow turbulence assumptions were adapted from previous works [5], [6].…”
Section: Equationsmentioning
confidence: 99%
“…Qiu et al [2,3] used porous copper as a substrate to prepare microchannel radiators with excellent heat dissipation capabilities, which allowed device temperatures to be reduced from 85℃ to 59℃ when using the optimal combination of pore size and porosity. Some researchers added different radiators [4] and nanoparticles [5] with different particle shapes to the coolant to form different nanofluids in place of water as the coolant that enhanced the heat transfer with obvious effect. Still, these methods greatly increased the difficulty of microchannel manufacturing and material costs.…”
Section: Introductionmentioning
confidence: 99%